Factors controlling hydrate film growth at water/oil interfaces. (2nd October 2015) - Li, Sheng-Li; Wang, Yun-Fei; Sun, Chang-Yu; Chen, Guang-Jin; Liu, Bei; Li, Zhi-Yun; Ma, Qing-Lan
Abstract: The methane hydrate film growth kinetics on the surface of water droplets suspended in n-octane was investigated. When the water droplet was suspended in n-octane unsaturated with methane, the hydrate formation behavior on its surface showed a hydrate curtain caused by the continuous forming, moving, and dissociating of hydrate crystals. When n-octane was saturated with methane, the lateral growth rates of the hydrate film were measured under different pressures. The mass transfer of methane molecules near the film front was suggested as the control step of lateral growth. For hydrate film growth in thickness, massive apophyses occurred and developed in the outer surface of the hydrate film, indicating an outward water transfer through the film. The sinking of the hydrate film caused by leaking of the inner water was observed. These two phenomena indicated the contribution of the outward growth of water through the hydrate film in thickening growth. Highlights: Methane hydrate film growth kinetics on the surface of water droplet suspended in oil was investigated. The lateral growth of hydrate film is controlled by mass transfer of methane molecules near film front. Hydrate film growth in thickness is controlled by the outward mass transfer of water through hydrate film. Hydrate formation behaviors on the surface of water droplets suspended in oil saturated and unsaturated with methane are different.